Memahami Instrumentasi Inovasi Kebijakan: Studi Policy Hackathon pada Program Cimahi Innovathon Days di Kota Cimahi - Purnomo, Dwi; Wicaksono, Ferdyansyah; Dante, Puntigavere; Purnama, Adet Chandra; Ayulinda, Dini (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2024)
This research explores the role of policy hackathons as an innovation instrument in public policy development through a case study of the Cimahi Innovathon Days program in Cimahi City. The background of this research is based on the need to understand how policy hackathons can produce relevant and sustainable policy solutions at the local level. The main objective of this research is to understand the context related to policy hackathons, which are still rarely discussed in practical terms in public policy case studies in Indonesia, as one of the methods in participatory public policy formulation. The methodology used is discourse analysis, which involves direct observation and interviews with the stakeholders involved. The research results indicate?that?the?implementation?of?policy?hackathons?can?be?one?alternative?for participatory policy formulation involving the general public. Additionally, focusing on the needs of citizens, responsible leadership, and measurable real-world impact are important factors in this process. The conclusion of this research underscores the great potential of policy hackathons in creating innovative solutions that can be effectively implemented at the local level. The practical implications of these findings include the importance of strengthening inter-sectoral collaboration in policy formulation and the need for ongoing evaluation of the long-term impacts of the resulting policies. This research also opens up opportunities for the development of new policy instruments that can be adopted in various other regions.